Constituency influence in Parliament : countering the centre - Blidook, Kelly (UBC Press, 2012)
Canada's parliamentary system has been characterized as 'executive-dominant, ' with governance focused on the 'centre, ' and scholars have paid little attention to the legislature and its members. Constituency Influence in Parliament illuminates how MPs, in their pursuit of various goals in the legislature, play an important representative role in shaping policy. This critical volume offers the first full-scale examination of the rules and conduct of parliamentary Private Members' Business and of the electoral and policy motivations of those who hold the country's highest elected office. Kelly Blidook offers a thought-provoking assessment of the representational and policy dynamics that exist within the Canadian institutional structure. His examination of what MPs do, why they do it, and what it effect it has, resurrects the relevance of Canada's Parliament"--Page 4 of cover.